Efficacy of Hot Alcoholic Peganum harmala seed Extract Against Oral Candida albicans and Candida tropicalis isolates from Children in Karbala Governorate, Iraq - Sadeq Hussein , Wafaa; Taha Mohmmed , Ban; A . Lahoof , Adnan (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Communicative microorganisms contribute to maintaining the balance of the oral environment, which is an open environment to the external environment, making it a vital and diverse environment that allows for the colonization of different types of microbes Candida, in particular, is one of the most common types of fungi and is considered a normal flora of the skin. Its overgrowth leads to the development of oral candidiasis, an opportunistic fungal infection that includes inflammation of the tongue and parts of the oral mucosa. Methodology: The study included obtaining 51 samples from children without genetic diseases from the wards of Karbala Teaching Hospital for Children, ranging in age from 16 days to 10 years. The samples were collected using cotton swabs containing a sample collection medium and transferred to the laboratory of the Imam Hussein Center for Manuscripts and Research. The samples were examined morphologically and microscopically, and some virulence factors were studied, and the inhibitory ability of the hot alcoholic extract of harmal seeds against the yeasts used in the study was tested. Results: The results of the study showed that 33 out of 51 samples were positive for Candida growth, representing 65%. C. albicans was recorded at 80% (24 isolates), and C. tropicalis numbered 6, representing 20%. These two Candida species were identified through the study of some morphological and microscopic characteristics, which showed that C. albicans appeared green color and C. tropicalis blue color on chromogenic agar. C. albicans was the most common species in the current study, characterized by its ability to produce germ tubes, hyphae, and Chlamydospore, unlike C. tropicalis, which was only capable of forming pseudo hyphae. The inhibitory activity of harmal seeds was tested, with the highest inhibitory activity recorded at a concentration of 100 mg/ml for both C. tropicalis and C. albicans, reaching inhibition rates of 20.4 and 15.9 mm, respectively. The lowest inhibitory activity was recorded at a concentration of 20 mg/ml for both C. tropicalis and C. albicans, reaching inhibition rates of 12.3 and 8.5 mm, respectively. The inhibition rate of the antifungal nystatin was 13.5 and 14.7 mm, respectively. Conclusions: C. albicans was one of the most common species in this study, as this species was distinguished by possessing a set of virulence factors .The plant (Peganum harmala L) is a medicinal plant with pharmaceutical properties and has proven its inhibitory efficiency against the species under study